2021
DOI: 10.3390/antibiotics10081020
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MRSA Cephalosporin versus Vancomycin-Based Treatment for Acute Bacterial Skin and Skin Structure Infection: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: This systematic review and meta-analysis of randomized controlled trials (RCTs) compared the clinical efficacy and safety of anti-MRSA cephalosporin and vancomycin-based treatment in treating acute bacterial skin and skin structure infections (ABSSSIs). PubMed, Embase, Cochrane Central Register of Controlled Trials, Turning Research into Practice, and ClinicalTrials.gov databases were searched for relevant articles from inception to 15 June 2020. RCTs comparing the clinical efficacy and safety of anti-MRSA cep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Primary analysis of Phase 3 studies utilizing ceftaroline when compared to standard treatments (including vancomycin or linezolid) indicate comparable outcomes for MRSA-related SSTIs [ 219 ]. Post-marketing analyses indicate similar treatment benefits with ceftaroline [ 220 ]. The most common side effects include rashes, pruritus, pyrexia, gastrointestinal intolerance, and infusion site reactions [ 197 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Primary analysis of Phase 3 studies utilizing ceftaroline when compared to standard treatments (including vancomycin or linezolid) indicate comparable outcomes for MRSA-related SSTIs [ 219 ]. Post-marketing analyses indicate similar treatment benefits with ceftaroline [ 220 ]. The most common side effects include rashes, pruritus, pyrexia, gastrointestinal intolerance, and infusion site reactions [ 197 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Likewise, the ceftobiprole in vitro potency has been demonstrated in several previous studies of globally sourced MRSA isolates [46,47]. Moreover, the clinical efficacy of ceftobiprole was shown to be comparable to that of vancomycin and vancomycin plus ceftazidime in the treatment of cSSTIs in two earlier phase III clinical trials (STRAUSS I and STRAUSS II) [48]. Additionally, a randomized double-blind multicenter trial (TARGET) comparing ceftobiprole monotherapy with vancomycin plus aztreonam demonstrated that ceftobiprole is noninferior to vancomycin plus aztreonam in the treatment of ABSSSIs, in terms of early clinical response [49].…”
Section: Discussionmentioning
confidence: 68%
“…In the study of Overcash et al, the microbiological response rates were generally similar between ceftobiprole and its comparators in patients with ABSSSIs caused by MRSA [49]. In addition, ceftobiprole shares a similar safety profile to its comparators [48,49].…”
Section: Discussionmentioning
confidence: 90%